Hubungan Perkembangan Guna Lahan dengan Peningkatan Aksesibilitas - Moh. Reza Rizqi P. Sangadji; Arifuddin Akil; Yashinta Kumala Dewi Sutopo (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2016)
The purpose of this research is, the magnitude of land use development in terms of function and land use area, explain the magnitude of increased accessibility in terms of the length of the road network, and explain the level of relationship between land use development and increased accessibility in Tamalanrea District, Makassar City. Data on land use development and increased accessibility in this study used data from 2004 to 2014. The data were analyzed using correlation analysis by linking the variables of land use development with increased accessibility. The results showed that the development of land use during the last 10 years generally showed a transition from less productive land use (gardens, ponds, fields, swamps, fields, empty land, rice fields, mangrove, settlements) to more productive land uses (trade and services , industry, offices, education, health, military) with a total land use development of 612 Ha. Increased accessibility over the past 10 years shows an increase in the length of the road network, which is 107 Km. The results of the correlation between land use development variables with increased accessibility amounted to 0.578. This value explains that the greater the development of land use, the higher the accessibility. The connection between the development of land use and increasing accessibility needs to be supported by the availability of good public transportation so that problems such as frequent disruption of transportation systems and other problems can be resolved.